Development of industrial air pollution monitoring system for safety and health enhancement and sustainable work environment in small and medium industries (SMI's) - Leman, Abdul Mutalib (2011)
The study is focused on the development of Industrial Air Pollution Monitoring System (IAPMOS) for small and medium industries application. The objectives of the study are to develop a system with special configuration on wireless data communications and able to analyze hazard and risk especially in welding process. The Quality Function Deployment (QFD) was used as a tool in the design the system. Questionnaires were distributed to the relevant personnel in manufacturing industries. Case study was carried out in two manufacturing companies located in Shah Alam, Selangor. Another case study on wireless data communication was conducted in the Walk-in Stability Chamber (WiSC) at Universiti Tun Hussein Onn Malaysia (UTHM). The system analyzed the data after save file and it is used the Hazard Risk Index (HRI) approach and the result on risk level were used Risk Classification Matrix (RCM) approach. The system features has warning sign (by colour) and buzzer to ensure the safety and health personnel gives attention to the outcome toxic gas data collection. The system can reach 150m length for accurate wireless data transfer. The IAPMOS can be used by the industries to create safe, healthy and sustainable work environment and reduce occupational diseases.